Rare case report of metastatic cervical carcinoma - Kamat, Amitha V.; Kittur, Sahaja S.; Hiremath, Mallikarjun G.; Sambrani, Annapurna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Although carcinoma of cervix is among the most common malignancies in women, cutaneous metastasis is very unusual. Here we report a case of a parous woman diagnosed with adenocarcinoma of cervix who did not undergo chemotherapy in spite of being advised after initial surgery, presenting with cutaneous metastasis at the operative scar site 2 years later.